Pendayagunaan Lahan Kosong untuk Meningkatkan Ekonomi Pesantren Mahasiswa Safinatun Naja Melalui Budidaya Ikan Nila dan Lele - Sri Haryanto (PT. Global Research Collaboration, 2024)
Community service with the title Empowerment of Empty Land to Improve the Economy of SafinatunNaja Student Boarding School through Tilapia and Catfish Cultivation aims to improve skills (soft skills) and economic strengthening in the agribusiness sector at PPTQ Safinatun Najah Kalibeber, Mojotengah Wonosobo Regency. The socio-religious and community roles have become an integral part of the boarding school community, Kiai, santri, and the surrounding social community really feel the touch of kiai and the existence of boarding schools as typical Indonesian educational institutions. In the current and strategic context, building the economic resilience of Islamic boarding schools is another thing that is no less important to pay attention to in the midst of an era of economic contestation that is increasingly hardening and tends to move away from ethical and moral values. Safinatun Naja Qur'anic Boarding School is located in a mountainous location, right under the foot of Mount Sindoro and Mount Bismo, 5 km from the centre of Wonosobo City. Judging from its natural resources, Pesantren Safinatun Naja has great potential in developing agribusiness skills and entrepreneurship, so it is necessary to provide assistance in order to empower Pesantren Safinatun Naja to become a centre for developing agribusiness entrepreneurship in the fisheries sector. The priority of this programme is the empowerment of community agribusiness entrepreneurship / PPTQ Safinatun Naja Kalibeber, Wonosobo in the fisheries sector, namely tilapia, catfish and melem cultivation and goldfish breeding, by utilising vacant land and fish ponds in the PPTQ Safinatun Naja environment.